Iconography of the Baptism Scene Developed from an Older Layer of Fresco Painting from around 1530 in the Gračanica Monastery Exonarthex - Dimitrijević, Aleksandra R. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
It is quite certain that the visible frescoes in the exonarthex of the Gračanica Monastery outer narthex do not come from the same period, so their chronological separation and more precise dating are complex. If it is taken into account that it was built in the early thirties of the 14th century, the outer vestibule have been painted after 1330, but those frescoes are not visible today. It was repainted later, during the time of Metropolitan Nicanor around 1530. The scene of the Baptism of Christ (Mt. 3: 13‒17, Mk. 1: 9‒11, Lk. 3: 21‒22, Jn. 1: 29‒34) belongs to the time of the Metropolitan Nicanor, and it is located on the eastern wall of the outer chancel, south of the southeastern pilaster. The iconographic analysis of this scene provides an insight into the wide theological education of the painters, as well as a sense of narrative and primarily adherence to good models from the Paleology era. The style of the Gračanica Monastery frescoes, which belong to the period around 1530, was adapted to the program based on tradition. The developed scene of the Baptism of Christ, inspired by the highest role models, emphasizes confidence in composition and performance, expert drawing and fine modelling in combination with an illuminated palette.
Keywords: Baptism of Christ; Metropolitan Nicanor; Gračanica Monastery exonarthex; Saint John the Baptist